2020
DOI: 10.3389/fonc.2020.00758
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological STING Activation Is a Potential Alternative to Overcome Drug-Resistance in Melanoma

Abstract: Melanoma is the most aggressive type of skin cancer and resistance to the conventional chemotherapy is the major cause for its poor prognosis. Metabolic perturbations leading to increased production of reactive oxygen species activate NRF2-dependent anti-oxidative responses to survive oxidative stress. This protective function of NRF2 is the primary cause for therapy resistance in cancer as anti-cancer agents such as BRAF inhibitors also induce NRF2-dependent antioxidative response. We had reported that type I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 32 publications
0
26
0
2
Order By: Relevance
“…However, the use of the STING agonist DMXAA combined with caspase inhibition in vivo increases TNF and IFN levels subsequently leading to necroptosis, but this resulted in increased mortality due to septic shock [74]. Although, DMXAA is a failure in clinics due to its inability to effectively activate human STING, small molecule STING agonist amidobenzimidazole (ABZI) has been reported to bind and activate both human and mouse STING [80,81]. Therefore, such STING agonists in clinical trials will need to be assessed for their roles in triggering necroptosis without extensive secondary effects.…”
Section: Interplay Between the Cgas-sting Signaling And Necroptosismentioning
confidence: 99%
“…However, the use of the STING agonist DMXAA combined with caspase inhibition in vivo increases TNF and IFN levels subsequently leading to necroptosis, but this resulted in increased mortality due to septic shock [74]. Although, DMXAA is a failure in clinics due to its inability to effectively activate human STING, small molecule STING agonist amidobenzimidazole (ABZI) has been reported to bind and activate both human and mouse STING [80,81]. Therefore, such STING agonists in clinical trials will need to be assessed for their roles in triggering necroptosis without extensive secondary effects.…”
Section: Interplay Between the Cgas-sting Signaling And Necroptosismentioning
confidence: 99%
“…Manganese potentiates the anti-tumor immune response as a STING agonist [ 107 ]. Dimeric aminobenzimidazole (diABZI) is another STING agonist that promotes tumor cell death in melanoma in combination with BRAF inhibitors [ 108 ]. Cytomegalovirus (CMV) acts as a STING agonist in tumors.…”
Section: Sting Strategy For Skin Cancersmentioning
confidence: 99%
“…Separate groups of researchers have reached an agreement that direct activation of STING can robustly block SARS-CoV-2 infection. Moreover, they found that the STING agonist, diABZI and diABZI-4, can effectively restrict SARS-CoV-2 replication ( Chipurupalli et al, 2020 ; Zhu et al, 2021 ). Furthermore, Wu et al (2021) expanded the function of a novel STING agonist, CDG SF , as an adjuvant for the SARS-CoV-2 vaccine.…”
Section: Severe Acute Respiratory Syndrome Coronavirus-2 Infection and Cyclic Gmp-amp Synthase-stimulator Of Interferon Genesmentioning
confidence: 99%